A polêmica como interincompreensão: construção negação de simulacros no campo discursivo da surdez (The polemic as an inter-incomprehension: construction and denial of simulacra in the discursive field of deafness) - Ribeiro, Maria Clara Maciel de Araújo (2015)
This study approach the phenomenon of discursive inter-incomprehension. Our goal is to observe the interaction that occurs between discourses polemics in the discursive field of deafness, which constituted a discursive space delimited by two distinct positions on deafness: Audism Based Discourse and Deaf Based Discourse. Analyses indicate that the first one will be by means of anticipation - and denial - of what could be his simulacrum to the second one. The DFS will be defined precisely from what it is not, in order to build an "I" from the denial of a "non-self."KEYWORDS: Discourse. Deaf. Simulacrum. Polemical discourse.